225k views
3 votes
Helppppppppppppppppppppp

Helppppppppppppppppppppp-example-1
User Anakic
by
5.0k points

1 Answer

4 votes

Answer: Choice D) x = -2(y+2)^2 - 3

=======================================

Step-by-step explanation:

One way to represent vertex form of sideways parabolas like this is to write

x-h = a(y-k)^2

where (h,k) is the vertex and 'a' determines how stretched out it is. All of the answer choices have a = -2, so we can ignore this value.

The vertex shown in the image is at (-3, -2). So this means (h,k) = (-3,-2) and furthermore h = -3 and k = -2.

Let's plug a = -2, h = -3 and k = -2 into the equation below and isolate x

x-h = a(y-k)^2

x-(-3) = -2(y-(-2))^2

x+3 = -2(y+2)^2

x = -2(y+2)^2 - 3

which is what choice D is saying

User RapGodRory
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.